Microsoft SQL server 2008 administration for Oracle DBAs [ - Anderson, Mark , 1977-; Bolton, Christian; Fox, James , 1976- (McGraw-Hill, 2011)
"An expert guide to working with SQL Server in a mixed-database environmentMicrosoft SQL Server Administration for Oracle DBAs is the ideal resource for experienced Oracle database professionals looking to expand their knowledge and skill set into the Microsoft database platform. The book compares and contrasts the platform architectures and shows how to perform everyday database administrator tasks. Screenshots, script examples, and step-by-step labs are included in this practical guide. This book is not designed to be a "SQL Server is better than Oracle" or vice versa. It will enable experienced Oracle database administrators to get up to speed on the Microsoft SQL Server platform by building on existing relational database skills. The authors? combination of expertise in both technologies ensures technical accuracy and real-world experiences. Interviews with members of the Oracle DBA community are included in this practical guide. Microsoft SQL Server Administration for Oracle DBAs is co-written by a data platform technical specialist at Microsoft, UK who works daily with large customers integrating SQL Server into Oracle. Teaches dual skills using real-world examples based on authors? vast experience. Quickly explains how to perform everyday database admin tasks on SQL Server. Focuses on making both platforms work together successfully. Includes step-by-step labs and interviews with members of the Oracle DBA community Leverage your Oracle DBA skills on SQL Server SQL Server Architecture; Installing and Configuring SQL Server; Database Objects; Security; Data Access and Transaction Control; Backup and Recovery; Performance Tuning and Optimization; High Availability and Disaster Recovery Options; Scheduling, Automation and Alerting; Data Movement; Upgrading and Migrating to SQL Server"-- Provided by publisher